Action plan for the management of special wastewater in the city La Libertad, El Salvador - Rosales-Ayala, Francisco (2020)
This article describes the preparation of an action plan to improve the management of wastewater of special type generated in the commercial sector of the city La Libertad, in El Salvador; as an academic contribution to development of competencies for environmental management in general and  management of special type wastewater, in particular. The methodology for the preparation of the action plan was participatory;  as a result, a management group was formed by stakeholders directly involved in the generation and management of wastewater The objective of the action plan is to reduce environmental pollution by special wastewater generated by the economic activity of the city La Libertad; and the plan is structured according to three areas of intervention: political, environmental education, and technical-scientific. Given the importance of environmental education, a pilot test was developed, that consisted of training workshops with sectors directly related to the generation and management of wastewater of special type.